VD_FINDINFO HC / 2014 / 564 vom 14. Mai 2014 - VD Tribunal cantonal (2014)
BAIL À LOYER, MOTIF, RÉSILIATION, ANNULABILITÉ, USAGE PERSONNEL, RÉNOVATION D'IMMEUBLE, PROLONGATION DU BAIL À LOYER | 271 al. 1 CO, 272 al. 1 CO, 272b al. 1 CO